Perspectives of the GAMMA-400 space observatory for high-energy gamma rays and cosmic rays measurements. Issue 3 (January 2016) - Topchiev, N P; Galper, A M; Bonvicini, V; Adriani, O; Aptekar, R L; Arkhangelskaja, I V; Arkhangelskiy, A I; Bakaldin, A V; Bergstrom, L; Berti, E; Bigongiari, G; Bobkov, S G; et al.
Abstract: The GAMMA-400 gamma-ray telescope is intended to measure the fluxes of gamma-rays and cosmic-ray electrons and positrons in the energy range from 100 MeV to several TeV. Such measurements concern the following scientific tasks: investigation of point sources of gamma-rays, studies of the energy spectra of Galactic and extragalactic diffuse emission, studies of gamma-ray bursts and gamma-ray emission from the Sun, as well as high precision measurements of spectra of high-energy electrons and positrons. Also the GAMMA- 400 instrument provides the possibility for protons and nuclei measurements up to knee. But the main goal for the GAMMA-400 mission is to perform a sensitive search for signatures of dark matter particles in high-energy gamma-ray emission. To fulfill these measurements the GAMMA-400 gamma-ray telescope possesses unique physical characteristics in comparison with previous and present experiments. The major advantage of the GAMMA-400 instrument is excellent angular and energy resolution for gamma-rays above 10 GeV. The GAMMA-400 experiment will be installed onboard of the Navigator space platform, manufactured by the NPO Lavochkin Association. The expected orbit will be a highly elliptical orbit (with apogee 300.000 km and perigee 500 km) with 7 days orbital period. An important profit of such an orbit is the fact that the full sky coverage will always be available for gamma ray astronomy.